2019
DOI: 10.1002/pon.5274
|View full text |Cite
|
Sign up to set email alerts
|

A summary of high quality online information resources for parents with cancer who have adolescent and young adult children: A scoping review

Abstract: Objective Parents with cancer want information about maintaining family functioning despite cancer. This scoping review assesses what online information resources are available to help parents with cancer maintain family functioning, the quality of the available information, and whether resources provide specific advice for parents of adolescent and young adult (AYA) children. Methods To identify available relevant English‐language online information resources, we imitated a parental online information search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Guidelines for conducting the review were documented and agreed to by the research team prior to conducting the searches. This guidance was modelled on methods used by Weeks et al [20]. Searches were run using Google and the top 30 results, or first three pages, of each were retained.…”
Section: Methodsmentioning
confidence: 99%
“…Guidelines for conducting the review were documented and agreed to by the research team prior to conducting the searches. This guidance was modelled on methods used by Weeks et al [20]. Searches were run using Google and the top 30 results, or first three pages, of each were retained.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was recommended by Godin et al, (2015) because it emphasizes relevancy rankings. Also, one study showed that people rarely go beyond the first or second page of an internet search, so including 100 entries is comprehensive (Weeks et al, 2019). Identifying and documenting what information exists via Internet search contributes to understanding what information is most accessible.…”
Section: Adaptations For Social Workmentioning
confidence: 99%
“…While many resources supporting parents with cancer in their relationship with their children exist internationally, a recent review found that most do not address all of the specific needs of AYA children, and none address the needs of young adult (18‐25 years) children 6 despite older AYAs experiencing higher levels of anxiety and depression 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…1. Review of existing resources : Online information 1 targeting parents with cancer was reviewed to assess the availability and quality of information resources supporting parents with AYA children to maintain family functioning 6 . We also reviewed resources developed internally for a clinical intervention to support families impacted by parental cancer 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation